The MultiDark Database: Release of the Bolshoi and MultiDark cosmological simulations. Issue 7 (1st August 2013) - Riebe, K.; Partl, A. M.; Enke, H.; Forero‐Romero, J.; Gottlöber, S.; Klypin, A.; Lemson, G.; Prada, F.; Primack, J. R.; Steinmetz, M.; Turchaninov, V.
Abstract We present the online MultiDark Database – a Virtual Observatory‐oriented, relational database for hosting various cos‐mological simulations. The data is accessible via an SQL (Structured Query Language) query interface, which also allows users to directly pose scientific questions, as shown in a number of examples in this paper. Further examples for the usage of the database are given in its extensive online documentation. The database is based on the same technology as the Millennium Database, a fact that will greatly facilitate the usage of both suites of cosmological simulations. The first release of the MultiDark Database hosts two 8.6 billion particle cosmological N‐body simulations: the Bolshoi (250 h–1 Mpc simulation box, 1 h–1 kpc resolution) and MultiDark Run1 simulation (MDR1, or BigBolshoi, 1000 h–1 Mpc simulation box, 7 h–1 kpc resolution). The extraction methods for halos/subhalos from the raw simulation data, and how this data is structured in the database are explained in this paper. With the first data release, users get full access to halo/subhalo catalogs, various profiles of the halos at redshifts z = 0–15, and raw dark matter data for one time‐step of the Bolshoi and four time‐steps of the MultiDark simulation. Later releases will also include galaxy mock catalogs and additional merger trees for both simulations as well as new large volume simulations with high resolution. This project is further proof of the viability to store and present complex data using relational database technology. We encourage other simulators to publish their results in a similar manner. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)